Intensive Rain Hampers the Effectiveness of Nitrification Inhibition in Controlling N2O Emissions from Dairy Slurry-Fertilized Soils - Jordi Escuer-Gatius; Merrit Shanskiy; Ülo Mander; Karin Kauer; Alar Astover; Hanna Vahter; Kaido Soosaar (Agriculture, 2020)
Nitrification inhibitors have been proposed as a tool to mitigate nitrous oxide (N2O) emissions from agriculture, which are caused mainly by fertilization. The nitrification inhibitor 3,4-Dimethylpyrazole phosphate (DMPP) was tested in a winter rapeseed field after dairy slurry application in Central Estonia. N2O emissions were monitored using the closed chamber method. Soil and leachate chemical parameters were also analyzed. N2O emissions increased from pre-slurry application values of 316 and 264 µg m−2 h−1 for the control and treatment plot, respectively, to maximum values of 3130.71 and 4834 µg m−2 h−1, with cumulative emissions during the study period of 12.30 kg ha−1 for the control plot and 17.70 kg ha−1 for the treatment plot. The intense precipitation period that began with the application of the slurry resulted in changes in soil moisture and water-filled pore space (WFPS), modifying the nitrification/denitrification balance. Positive significant correlations (p = 0.016 and p = 0.037, for the control and treatment plot, respectively) were found between N2O fluxes and WFPS. Future studies should consider the role of nitrifier and denitrifier communities in order to better assess in-field nitrification inhibitor effectiveness.